An Assessment of Health-Related Quality of Life (HRQoL) among the Married Women in Rural Areas of Koch Bihar District, West Bengal, India - Karimul Islam; Tarun Das (Journal of Geographical Studies, 2026)
The health-related quality of life (HRQoL) of married women in rural areas is influenced by a range of socio-economic and health factors. This study aims to assess the HRQoL among married women residing in the rural areas of Koch Bihar district, West Bengal. A total of 569 married women were selected using a simple random sampling method from 58 villages across all 12 blocks of the district. Data were collected through a structured interview schedule designed to capture information on various dimensions of HRQoL. The findings reveal that rural married women face multiple challenges that impact their physical, psychological, social and environmental well-being. The study highlights significant variations in HRQoL scores based on age, education, economic status and access to health care services. The results emphasize the need for targeted interventions to address the specific needs of rural women, particularly in improving access to health care, education and economic opportunities. This research provides valuable insights for policymakers and public health professionals aiming to enhance the overall well-being of women in rural settings.